RISK OF ANTERIOR CRUCIATE LIGAMENT INJURY IN FEMALE SOCCER ATHLETES: SYSTEMATIC REVIEW - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Women's soccer is quickly becoming one of the most popular sports in the world. The quick acceleration and deceleration of many joints in the lower limbs is required for many of the common movements that occur during play, such as jumping and cutting. During these activities, participants frequently sustain injuries to the anterior cruciate ligament (ACL), which is one of the factors that contributes to the knee's overall stability. Injuries to the ACL almost always call for expensive surgery, significant time away from athletics, and put the long-term health of the joint at jeopardy. Women are more likely to suffer an ACL tear than men because of anatomical differences and gender-specific variables, such as menstruation. Injuries frequently occur in situations when there is no physical contact, typically as a result of rapid acceleration or deceleration motions. These motions have been the subject of research, which has uncovered a number of kinematic and kinetic mechanisms, in addition to muscle activation patterns that typically take place during the moment of injury; however, the findings tend to vary from population to population. This article provides a summary of recent and important research on the mechanisms of ACL injuries, and it also draws attention to the dearth of particular research on high-risk populations of female soccer athletes. Injury prevention strategies among this demographic have been all over the place because the risk variables have not been conclusively determined. The possibility of female soccer players sustaining an injury to their ACL needs to be investigated more thoroughly in order to identify more specific injury risks and devise more effective preventative strategies. A greater awareness of this need may attract the attention of the scientific and medical communities, which may, in turn, drive the development of measures that prevent future ACL injuries and, as a result, the issues that these injuries provide to high-risk female soccer athletes.